Study the influence of seaweed compost mixtures on germination of carob (Ceratonia siliqua L.) seeds - منصور, ريم; حسن علاء الدين ,; أمين صالح, (Latakia University Journal -Biological Sciences Series, 2024)
The aim of this research is to investigate the possibility of using fermented seaweed and its mixtures with agricultural soil in proportions (1/2, 1/3, 1/4) on the plant as a planting medium in forest nurseries compared with the control medium (agricultural soil) and the studied plant material, Ceratonia siliqua L. This research was conducted during the year 2020-2021 at the Boga Botanical Center of the Faculty of Agriculture at Tishreen University. The results of the research showed that the process of mixing seaweed compost with the agricultural soil increased the germination rate compared to the control and with the compost medium alone, and this means that the basic media alone and their mixtures are suitable for being a good medium for germination of carob seeds. The results also showed that the average shoot length was the best in the treatments of mixing compost with agricultural soil compared to the control and compost alone, and the mixing of compost with agricultural soil improved the dry weight values ​​of the shoot and root groups compared to the compost control and alone, and that the best values ​​for R / S (length, weight) in the two treatments (mixing compost with agricultural soil 1/3, 1/4).